Simulation Study on Electrical Resistance Tomography using Metal Wall for Bubble Detection - Suzanna Ridzuan Aw; Ruzairi Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Elmy Johana Mohamad; Fazlul Rahman Mohd Yunus; Yasmin Abdul Wahab; Naizatul Shima Fadzil; Juliza Jamaludin (Penerbit UTM Press, 2024)
Indexed by MyCite